Service Line Material Identification: Experiences From North American Water Systems. Issue 1 (18th January 2022) - Liggett, Jennifer; Baribeau, Hélène; Deshommes, Elise; Lytle, Darren A.; Masters, Sheldon V.; Muylwyk, Quirien; Triantafyllidou, Simoni
Key Takeaways: Under the Lead and Copper Rule Long‐Term Revisions, community water systems must establish an inventory of their lead service lines (LSLs); thus, the material used for every service line must be identified. Developing, using, and managing an LSL inventory involves multiple steps, resources, and components, and the resulting information needs to be accurate. An AWWA subcommittee interviewed 10 water systems to learn about their processes for LSL inventory creation, material identification, customer communication, and other aspects of their experiences.